Political leadership and the construction of competitive authoritarian regimes in Latin America: implications and prospects for democracy. Issue 3 (3rd April 2018) - Balderacchi, Claudio
ABSTRACT: Recent developments have raised new concerns regarding the prospects of democracy in Latin America, particularly in what are often defined, although not unanimously, as cases of competitive authoritarianism, including Bolivia, Ecuador, Venezuela, and Nicaragua. In light of their significance and diffusion on a global level, understanding how these regimes emerge is important, especially when they replace democratic or imperfectly democratic regimes such as in the cases examined in this study. What explains the emergence of competitive authoritarian regimes (CARs), particularly when the starting point is democratic or imperfectly democratic? What are the region's democratic prospects after the emergence of various CARs in the last two decades? Through the comparative analysis of competitive authoritarian attempts in Bolivia, Ecuador, Honduras, Nicaragua, and Venezuela, I argue that the same passages and challenges required to transform a democratic regime into a CAR makes incumbents' features and strategies particularly important, especially the ability to weather potentially lethal institutional crises and limit the legitimacy costs associated with competitive authoritarian manipulations. Incumbents have proved more successful in these challenges and hence in their competitive authoritarian attempts when combining charisma and the elaboration of a democratic discourse including the diffusion of new democratic values.